2018
DOI: 10.1149/2.0621803jes
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lewis Acids on Graphite-Electrode Properties in EC-Based Electrolyte Solutions with Organophosphorus Compounds

Abstract: Compatibility of self-extinguishing property and electrochemical stability of electrolyte solutions containing organophosphorus compounds as flame retardants has been required for practical application of electrolyte solutions to lithium-ion batteries. By adding a Lewis acid, Ca 2+ , Mg 2+ , or Na + , to ethylene carbonate (EC)-based electrolyte solutions containing 50 vol.% trimethylphosphate or dimethyl methylphosphonate, the electrolyte solutions are able to suppress the co-intercalation of the organophosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 31 publications
2
16
0
Order By: Relevance
“…Ethylene carbonate (EC) is the most commonly used cosolvent in the electrolyte and its discovery is one of the greatest achievements contributing to the commercialization of lithium-ion batteries (LIBs). This is because the high dielectric constant of EC can help dissociate metal salts (e.g., LiPF 6 ) efficiently, while the reduction of EC can also form a requested solid electrolyte interphase (SEI) on the electrode surface for higher stability. Particularly, the EC-based electrolyte is effective at suppressing the graphite anode exfoliation (i.e., caused by the Li + –solvent coinsertion) compared to that of the PC-based electrolyte reported earlier. This is because a robust and/or durable SEI layer can be formed on the electrode surface as a result of EC-based electrolytes decomposition. These effects result in better battery stability and lifetime. These two commonly believed roles of EC are popular in the LIBs community and have been invoked in the electrolyte studies of current sodium and potassium (ion) batteries. …”
mentioning
confidence: 99%
“…Ethylene carbonate (EC) is the most commonly used cosolvent in the electrolyte and its discovery is one of the greatest achievements contributing to the commercialization of lithium-ion batteries (LIBs). This is because the high dielectric constant of EC can help dissociate metal salts (e.g., LiPF 6 ) efficiently, while the reduction of EC can also form a requested solid electrolyte interphase (SEI) on the electrode surface for higher stability. Particularly, the EC-based electrolyte is effective at suppressing the graphite anode exfoliation (i.e., caused by the Li + –solvent coinsertion) compared to that of the PC-based electrolyte reported earlier. This is because a robust and/or durable SEI layer can be formed on the electrode surface as a result of EC-based electrolytes decomposition. These effects result in better battery stability and lifetime. These two commonly believed roles of EC are popular in the LIBs community and have been invoked in the electrolyte studies of current sodium and potassium (ion) batteries. …”
mentioning
confidence: 99%
“…Solid–electrolyte interphase (SEI) formation on the electrode interface has become an omnipotent explanation for the improved performance of electrodes in rechargeable batteries. There is a consensus that the SEI is formed by electrolyte decomposition in the initial cycles and thus reduces the contact area of the electrode and electrolyte for mitigated side reactions. This belief is particularly popular regarding the graphite anode in commercial lithium-ion batteries (LIBs). This is because SEI formation is considered to be a positive effect that improves the first Coulombic efficiency (i.e., mitigating electrolyte decomposition) and enhances the compatibility of graphite with electrolyte, achieving highly reversible Li + (de)­intercalation. This SEI formation is additionally believed to suppress Li + –solvent co-insertion into graphite in propylene carbonate (PC)-based electrolyte, thereby avoiding the well-known graphite exfoliation process. In addition, the positive effect of SEI for the improved stability of the cathode (e.g., LiNi 1– x – y Co x Mn y O 2 , NCM) has also been widely reported. …”
mentioning
confidence: 99%
“…In this study, we found potassium bis­(trifluoromethanesulfonyl)­amide (KTFSA) with fewer Lewis acid K + than Na + demonstrated a superior Coulombic efficiency in the first charge-discharging process. However, the improvement in Coulombic efficiency by adding KTFSA has not been known yet, and we could not simply interpret improvement based on our previous study on salts with strong Lewis acids . Therefore, we investigated the dominant factor to improve the Coulombic efficiency by adding KTFSA.…”
Section: Introductionmentioning
confidence: 99%
“…However, conventional alkyl carbonate-based electrolyte solutions in lithium-ion batteries can easily catch fire in air. Recently, a flame retardant electrolyte solution has been achieved by including organophosphorus compounds, such as phosphates, phosphonates, , and phosphazenes. , In particular, trimethylphosphate (TMP) suppresses the flammability of electrolyte solutions when the TMP content is 30% or more in an ethylene carbonate (EC) and ethylmethyl carbonate (EMC) mixed solution . However, TMP tends to cointercalate with lithium ions into the graphite anode because its donor number is higher than that of EC, resulting in continuous decomposition and a large irreversible capacity loss during the initial cycling. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation